Sexual and Reproductive Rights and gendered cultural resistances in Western Africa, inequality, violence and illegitimacy - Carvalho, C.; Falcão, Ricardo (II Conferência Internacional Ativismos em África, 2019)
This paper bears the same name as the project on which it is based. The project aim is to analyse the intersection of gender and human rights in two West African countries, Senegal and Guinea Bissau, hopefully with a comparative lenses . It focus on body politics and it is interested in the way these societies refashion ideologies and social values to integrate gender equality and other human rights reccomendations. For that it has chosen to focus on the study of sexual and reproductive rights, but also on the myriad of activisms (NGO’s, citizen’s movements, religious movements) associated with them. By choosing such a focus this project aims at contributing to a better understanding of the processes of dissemination, or resistance to, human rights. The juridico-political nature of international instruments of human rights is, when translated locally, vernacularized – to use Sally Engle Merry’s expression - and it often induces forms of biopolitics that intersect with local practices and claim social legitimacy. This seems especially true in societies where there are social hierarchies